Mechanisms of Including the Skills of 21st Century in the Educational Competencies of the Basic Education Stage: Kingdom of Bahrain as an Example (Journal of the College of Education for Women, 2022)
The study aims to set an image to the mechanisms of the skills of the 21st century in the educational competencies of the basic education stage. To achieve this aim, a qualitative research design has been adopted in its analytical content analysis way. The study has arrived to the following conclusions:  the availability of: the communicative and team work skills with a percentage of 25.9%, linguistic competency with a percentage of 24.6%, the skills of local and global citizenship, creativity, and problem solving with a percentage of 13.6%, critical thinking with a percentage of 10.38%, technological culture with a percentage of 5.8%, pioneerism and initiativeness with a percentage of 10.38%, technological culture with a percentage of 3.8%, leadership and decision making with a percentage of 1.9%, the competencies of mathematics, which is mostly full of skills-  with a percentage of 37.5%%, Arabic language with 32.3%, English language with 13.5%, and science with 16.5%. As for the competencies attached to the third circle, they are considered highly full of skills with a percentage of 38.35, followed by the first circle with a percentage of 31.8%, and finally come the competencies attached to the second circle with a percentage of 29.8%. Based on these results, the research has set qualitative and quantitative mechanisms to include the skills of the 21st century regarding the educational competencies. It has further recommended checking the main and subsidiary educational competencies of the other subjects and the competencies of the secondary education to maintain including all the skills of the 21st century.